1991
DOI: 10.1037/0022-0167.38.4.487
|View full text |Cite
|
Sign up to set email alerts
|

Mexican Americans' initial preferences for counselors: The role of ethnic factors.

Abstract: In 3 studies, Mexican-American college students reported a clear preference for ethnically similar counselors. These findings are robust because they pertain to both men and women, they pertain to persons who have and have not sought counseling, they are not significantly influenced by the experimenter's ethnicity, and they apply to students who have considered professional help for a wide range of personal problems. Furthermore, the 3rd study demonstrated that these preference ratings are unlikely to be a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
2
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(93 citation statements)
references
References 22 publications
4
83
2
1
Order By: Relevance
“…This finding is in accord with research demonstrating that acculturation level has a significant effect on ratings of counselor trustworthiness and understanding among Hispanic students (Lopez, Lopez, & Fong, 1991;Pomales & Williams, 1989) and that acculturation is a predictor of attitude toward utility of mental health service among Chinese Americans (Ying & Miller, 1992).…”
Section: Introductionsupporting
confidence: 81%
“…This finding is in accord with research demonstrating that acculturation level has a significant effect on ratings of counselor trustworthiness and understanding among Hispanic students (Lopez, Lopez, & Fong, 1991;Pomales & Williams, 1989) and that acculturation is a predictor of attitude toward utility of mental health service among Chinese Americans (Ying & Miller, 1992).…”
Section: Introductionsupporting
confidence: 81%
“…Results suggested that clients generally express a greater preference for a counselor who is ethnically similar (Atkinson, Poston, Furlong, & Mercado, 1989;Bennett & BigFoot-Sipes, 1991;Sánchez & Atkinson, 1983). By contrast, Lopez, Lopez, and Fong (1991) reported that when a group of potential Mexican American clients rated the credibility of ethnically similar and dissimilar counselors, there was no difference. Additionally, Helms and Carter (1991) reported that racial identity and demographic models operate differently in different racial groups regarding preferences for similarity of various demographic variables.…”
Section: Cultural Competency In Psychotherapy and Counselingmentioning
confidence: 74%
“…5,7,8 Several studies have shown that minorities are more likely to select clinicians who mirror their own racial or ethnic background. 5,[9][10][11] The clinician's ability to speak the patient's language is a significant consideration in the patient's choice. 5,11 Racial and ethnic minorities are generally more satisfied with the care received from minority physicians.…”
Section: Building the Case For Diversity And Fostering Cultural Compementioning
confidence: 99%